IMPROVING ENERGY EFFICIENCY IN LOCAL WATER SUPPLY SYSTEMS USING PNEUMATIC TANKS AND PUMPS WITH VARIABLE FREQUENCY DRIVE (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
This article discusses the possibility of joint use of pneumatic tanks and pumps with an adjustable drive in local water supply systems. An overview of existing studies and existing methods for calculating pneumatic accumulators, as well as their effectiveness, is presented. The results of bench tests of pneumatic tanks and pumps with an adjustable drive are presented in order to determine the most effective areas of their operation. Further steps for research in this area are outlined.
Keywords: pneumatic tank; pump; pressure; forecasting; frequency converter; power; energy